Perturbing electron carriers of green algae Chlamydomonas reinhardtii for efficient physiological and metabolic regulation. Issue 2 (21st April 2022) - Zhou, Dongqing; Luo, Yeling; Zhang, Yingqiu; Zhao, Chenni; Wu, Hui; Fan, Jianhua
Abstract: Microalgae are widely used in the field of food bioengineering. There are relatively few studies on the synthesis of intracellular electron carriers in microalgae and their related metabolic effects. In this study, overexpression of Geranyl diphosphate: 4‐hydroxybenzoate geranyltransferase ( lepgt ), and the addition of 4‐hydroxybenzoic acid (4‐HB) as quinone ring precursor were adopted to regulate intracellular plastoquinone (PQ) and ubiquinone (UQ) levels in model algae Chlamydomonas reinhardtii . Small changes in PQ and UQ contents could regulate cell growth and metabolism. The expression of lepgt in C. reinhardtii significantly reduced the intracellular contents of PQ and UQ by 49.14% and 98.30%, respectively. The expression of lepgt observably reduced the photosystem activity and respiration rate and increased the contents of neutral lipid and starch by 63.68% and 19.42%, respectively. Exogenous low concentration of 4‐HB (1 mM) can effectively improve the contents of intracellular electron carriers, promote respiration, slightly reduce photosystem efficiency, and increase the maximum specific growth rate by 16.93%. It decreased the protein and oil contents by 15.48% and 15.10%, as well as changed the composition of long‐chain fatty acids. This paper provided a novel strategy for developing microalgal cell factories for future food production by perturbation on electron carriers of green algae. Abstract : Precise regulation of microalgae growth and product synthesis is an effective means to realize microalgal food and other application development. The genetic engineering and compound addition strategies in this study provided new strategies and methods for regulating the anabolism of active substances in microalgae.